"I like to use but do not wish to own": Exploring the role of de-ownership orientation in the adoption of access-based services. (July 2022) - Khalek, Sk Abu; Chakraborty, Anirban
Abstract: Consumers' outlook towards acquisition-based consumption is changing, and the importance of ownership is fading. Using the stimulus-organism-response framework and a total of 302 responses, this study employed partial least squares structural equation modelling (PLS-SEM) to examine the role of de-ownership orientation in the adoption of access-based services. The results show that de-ownership orientation positively influences access-based services' attitude and adoption intention. Further, it shows that stimuli such as ownership burden, economic benefits, environmentalism, and product scarcity risk influence de-ownership orientation. The findings contribute to understanding this emerging phenomenon of sharing economy. Highlights: Consumption preferences are shifting from possession to utility. Perceived hassles of ownership and economic incentives increase preference for non-ownership. De-ownership orientation drives consumers to adopt the 'access rather than own' consumption model. The findings would help access-based service providers to crystallize and communicate their value proposition effectively.